Women in antiquity (Lanham, Maryland ; New York, NY)
xi, 311 sayfa
Keywords: “Archaeology is one of our most powerful sources of new information about the past, about the lives of our ancient and not-so-ancient ancestors. The contributors to Women in Antiquity consider the theoretical problems involved in discerning what the archaeological evidence tells us about gender roles in antiquity. The book includes chapters on the history of gender research, historical texts, mortuary analysis, household remains, hierarchy, and ethnoarchaeology, with each chapter teasing out the inherent difficulty in interpreting ancient evidence as well as the promise of new understanding. Women in Antiquity offers a fresh, accessible account of how we might grasp the ways in which sexual roles and identities shaped the past“ --